Bank Al-Maghrib communication: A new evaluation of the power of monetary and economic transparency - El HIRI, Abderrazak; habiby, salwa (Archives of Business Research, 2018)
Theoretical arguments indicate that transparency could increase the credibility of low-inflation monetary policy, ameliorate the performance of decision-making and enhance the efficiency of interest rate setting. However, the qualitative nature of the communication makes its assessment difficult. The purpose of this article is to propose a new method of quantifying the information contained in central bank press releases and to examine whether the words spoken by policymakers can influence future monetary policy decisions in addition to macroeconomic variables. Through discourse analysis, we compared the importance attached to price stability and production. Then we developed a specific dictionary to measure Bank Al-Maghrib’s communication and finally, we examined the utility of transparency in predicting monetary decisions by exploiting the prospective Taylor rule. By creating two indicators of transparency (monetary and economic), we find that central bank governor statements are significantly related to future interest rate decisions. This approach should improve the ability of market participants to predict interest rate decisions and reinforce the emphasis placed on the information in the Taylor rule in addition to anticipating inflation and production, especially that Morocco is considering the transition to an inflation-targeting regime.